Pengaruh Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Restoran Chickenday Trenggalek - Sinta Fatmala Sari; Diana Ambarwati; Angga Permana Mahaputra (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
This study aims to determine the effect of product quality and service quality on consumer purchasing decisions, both partially and simultaneously, at Chickenday Restaurant Trenggalek. The method used is a quantitative approach with data processing in numerical form to objectively test the relationship between variables. The research was conducted at Chickenday Restaurant, located on Jl. Soekarno Hatta No. 20 Trenggalek. The research population consists of all consumers during the period of May–June 2025, the exact number of which is unknown. The sampling technique utilized probability sampling with a simple random sampling method, resulting in 96 respondents based on the Lemeshow formula. The data include primary data through questionnaires and observations, as well as secondary data from various sources. Data analysis was performed using multiple linear regression, t-test, and F-test. The results indicate that product quality and service quality have a positive and significant effect on purchasing decisions, both partially and simultaneously, with service quality being the more dominant variable.